Beyond "No Viral, No Justice": Rebuilding Institutional Legitimacy in Indonesia's Digital Society Public Trust, the Rule of Law, and Access to Justice in the Age of Digital Public Pressure - Anas Lutfi; Aris Mahmud (Greenation International Journal of Law and Social Sciences, 2026)
This research examines the significance of standard language in agreements and its impact using a qualitative descriptive method. The qualitative descriptive method was selected to provide a comprehensive and in-depth understanding of the complexities between language and the law. This study analyzes agreements to identify the use of standard language and its effect on legal interpretation. The study demonstrates the importance of standard language in agreements, as language influences legal consequences through word choice and sentence structure. These conclusions contribute to an understanding of how standard language affects the law. The use of the Indonesian language in agreements within Indonesia must pay heed to clarity, consistency, and the accuracy of legal terms. The use of non-standard language in agreements can result in several serious legal consequences. The implication is that this study may assist legal practitioners in drafting agreements. This research is significant to the literature on language and law, emphasizing the importance of standard language in agreements.